Remarks on "Solubilities of p-coumaric and caffeic acid in ionic liquids and organic solvents". (April 2019) - Xu, Renjie; Xue, Jin; Huang, Chunjuan; Zhao, Hongkun
Highlights: Errors are discovered in the published equation coefficients for NRTL model. Published equation coefficients fail to describe the reported mole fraction solubility. RTTL equation coefficients were re-analyzed. Abstract: Errors were discovered regarding the published equation coefficients of Alevizou and co-workers [J. Chem. Thermodyn. 62 (2013) 69–78] for mathematically describing the solubility of p -coumaric and caffeic acid in ionic liquids and organic solvents using the NRTL model. The curve-fit coefficients fail to describe the reported solubility data in the authors' published paper. The equation parameters were re-analyzed based on the reported solubility data.